2013
DOI: 10.1007/s00204-013-1046-0
|View full text |Cite
|
Sign up to set email alerts
|

Global and MGMT promoter hypomethylation independently associated with genomic instability of lymphocytes in subjects exposed to high-dose polycyclic aromatic hydrocarbon

Abstract: Global hypomethylation, gene-specific methylation, and genome instability are common events in tumorigenesis. To date, few studies have examined the aberrant DNA methylation patterns in coke oven workers, who are highly at risk of lung cancer by occupational exposure to polycyclic aromatic hydrocarbons (PAHs). We recruited 82 PAH-exposed workers and 62 unexposed controls, assessed exposure levels by urinary 1-hydroxypyrene, and measured genetic damages by comet assay, bleomycin sensitivity, and micronucleus as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 35 publications
5
41
0
Order By: Relevance
“…1 Overview of mechanisms through which air pollutants may act on the epigenome and subsequent disease risk Agency for Research on Cancer (IARC) [21,22]. When metabolized, PAHs can form DNA adducts and induce global hypomethylation and hypermethylation of specific genes associated with increased risk of neural impairments, neoplasia, and carcinogenesis [18,20,23,24].…”
Section: Pah B[a]p and Dna Methylationmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Overview of mechanisms through which air pollutants may act on the epigenome and subsequent disease risk Agency for Research on Cancer (IARC) [21,22]. When metabolized, PAHs can form DNA adducts and induce global hypomethylation and hypermethylation of specific genes associated with increased risk of neural impairments, neoplasia, and carcinogenesis [18,20,23,24].…”
Section: Pah B[a]p and Dna Methylationmentioning
confidence: 99%
“…Such epigenetic alterations are increasingly recognized as potential important mediators of health effects in the context of environmental or occupational settings that have high levels of PAHs. Several occupational studies, including studies of coke oven workers and steel, oil refinery, and petrochemical complexes, have observed associations between high levels of PAH exposure and LINE-1 hypomethylation [21,22,27].…”
Section: Pah B[a]p and Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the causative mechanisms of PAH-related health effects on the molecular level are not yet completely understood, PAHs exposure induced hypo-and hypermethylation at multiple promoter regions, suggesting that epigenetic modulation of genes may be a key mechanism (AlegriaTorres et al, 2013;Duan et al, 2013;Hew et al, 2015;Pavanello et al, 2009;White et al, 2016;Yang et al, 2012). Therefore, in this study, we evaluated if concentrations of PAHs in visceral AT were related to the methylation status of 12 key genes involved in glucose and lipid metabolism by using methylation-specific PCR (MSP).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, increased methylation of tumor suppressor genes, typically indicative of the gene being ‘silenced,’ has been considered to be relevant to cancer incidence [13] and has been demonstrated to be associated with breast cancer clinical/pathological factors and mortality in this study population [14]. Previous research has found that exposure to PAH may be associated with changes in DNA methylation [15-17]. …”
mentioning
confidence: 95%